Identifikasi Manifestasi Panas bumi Berdasar Interpretasi Citra di Daerah Manokwari, Provinsi Papua Barat - Pribowo Angling Kusumo; Agustinus Denny Unggul Raharjo (invotek, 2019)
Remote sensing is a science or arts to acquired information on object, area, as well as certain phenomenon without direct contact with the object, area or the phenomenon. Thus for geothermal manifestation phenomenon, ones could obtain the data by means of remote sensing using satellite; the data would be satellite image. The study was conducted on area of Kebar District, Manokwari Kabupaten, Papua Barat Province to obtain new possible geothermal manifestation on the area. The data used where ASTER L1B, SRTM image, and RBI map. The data were processed as follow: Delineation evaluation, NDVI Analysis, Surface temperature spreading analysis, and classification. from the data processing, the study found several new geothermal manifestations at Kebar Dsitrict, Manokwari Kabupaten, Papua Barat Province.